PTH-083 From paris to montreal: evolution of crohn's disease location and behaviour from childhood to adulthood. (June 2019) - Davies, Mike; Dodd, Susanna; Coultate, Morwenna; Ross, Andrew; Pears, George; Gnaneswaran, Bruno; Collins, Paul; Smith, Philip; Subramanian, Sreedhar
Abstract : Introduction: Crohn's disease (CD) is a progressive disorder but the natural history among paediatric onset CD appears different to that of adult onset CD. The long term disease evolution among paediatric onset CD beyond the childhood years is not well characterised. We conducted a single centre cohort study of all paediatric CD patients transitioned to adult care to assess the long term evolution of CD. Method: We conducted a retrospective observational, study of all CD patients diagnosed in childhood who were subsequently transferred to the care of an adult gastroenterology unit and had a minimum follow up of 2 years. We examined the case notes for evolution of disease location and behaviour. Disease location and behaviour was characterised using Paris classification at diagnosis and Montreal classification at last follow-up. In addition, we examined variables associated with the need for CD related intestinal resection. We used a paired McNemar's test to compare disease location and behaviour at diagnosis and most recent follow-up. Results: In total, 132 patients were included with a median age at diagnosis of 13 (IQR 11–14) and a median follow up of 11 years (range 4–14). At diagnosis, 23 (17.4%), 39 (29.6%) and 70 (53%) patients had ileal, colonic and ileocolonic disease. In addition, 31 (23.5%) patients had L4a or L4b disease at diagnosis (proximal or distal to the ligament of treitz respectively) and 13 patients (9.8%) had both whilst 27 (20.4%) patients had perianal disease. At diagnosis, only 27 (20.4%) patients had complicated disease behaviour at diagnosis. At the most recent follow-up, the median age was 23.5 (IQR 20–26). Disease location at follow-up was ileal location in 35 (26.5%), colonic in 36 (27.3%) and ileocolonic in 55 (41.7%). Upper GI disease was noted in significantly fewer patients (21, 15.9%, P=0.0018) while 31 patients (23.5%) had perianal disease. More patients had complicated disease behaviour (46 patients, 34.9%, P=0.0001). The mean time to start of thiopurines was 2 years (SD 4.2) and to biologics was 6 (SD 5) years and overall 121 (91.7%) and 84 (63.6%) were exposed to thiopurines and biologics respectively. The cumulative probability (95% CI) of surgery was 0.05 (0.02, 0.11) at 1 year, 0.17 (0.11, 0.24) at 3 years and 0.22 (0.15, 0.30) at 5 years. Neither disease location nor behaviour were associated with the need for intestinal resectional surgery. Conclusion: Over the course of an extended follow-up period, there appeared to be changes in both disease location and behaviour in paediatric onset CD. A high rate of exposure to thiopurines and biologics were noted in this cohort. We were unable to identify any variables associated with the need for intestinal surgery.